Modeling the Nucleus Laminaris of the Barn Owl: Achieving 20 ps Resolution on a 85-MHz-Clocked Digital Device - Salomon, Ralf; Heinrich, Enrico; Joost, Ralf (Frontiers in Computational Neuroscience, 2012)
The nucleus laminaris of the barn owl auditory system is quite impressive, since its underlying time estimation is much better than the processing speed of the involved neurons. Since precise localization is also very important in many technical applications, this paper explores to what extent the main principles of the nucleus laminaris can be implemented in digital hardware. The first prototypical implementation yields a time resolution of about 20 ps, even though the chosen standard, lowcost device is clocked at only 85MHz, which leads to an internal duty cycle of approximately 12 ns. In addition, this paper also explores the utility of an advanced sampling scheme, known as unfolding-in-time. It turns out that with this sampling method, the prototyp can easily process input signals of up to 300MHz, which is almost four times higher than the sampling rate.